1993
DOI: 10.1103/physrevc.48.2510
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of theHe4(γ,p0<

Abstract: A direct measurement of the He(y, po) reaction was performed using 34 MeV end-point bremsstrahlung photons. Photoprotons were simultaneously detected at nine angles. The magnitude of the deduced cross section is at variance with the results from recent experiments but is in perfect agreement with the previously recommended values. Consequently, as yet no definite conclusion can be drawn about the validity of charge symmetry of the nuclear force.The question of the absolute magnitude of the "He(y, po) reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
20
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…[I] were determined from in ditidual measurements of the (y,p) and (y, n) channels separately. Since this review, three new measurements of the proton channel have been reported [6][7][8]. The data from [6,7] are more consistent with the recommended photoneutron cross section, while [8] reports a cross section nearly twice as large, in agreement with the recommended proton cross section.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…[I] were determined from in ditidual measurements of the (y,p) and (y, n) channels separately. Since this review, three new measurements of the proton channel have been reported [6][7][8]. The data from [6,7] are more consistent with the recommended photoneutron cross section, while [8] reports a cross section nearly twice as large, in agreement with the recommended proton cross section.…”
mentioning
confidence: 66%
“…Since this review, three new measurements of the proton channel have been reported [6][7][8]. The data from [6,7] are more consistent with the recommended photoneutron cross section, while [8] reports a cross section nearly twice as large, in agreement with the recommended proton cross section. The only new published neutron data are from a capture reaction [9] which finds a peak cross-section value that is consistent with the recommended neutron value.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The 4 He(γ,p) 3 H cross section, σ(γ, p), was measured by detecting the protons by means of a NE213 liquid scintillator [11] and/or a Si(Li) detector array [12]. Note that the latest result by Hoorebeke et al using 34 MeV endpoint bremsstrahlung photons [12] is larger than the data by Bernabei et al [11] using a monochromatic photon beam by about 40% at around 30 MeV. The difference of these two data sets, however, becomes smaller with increasing the γ-ray energy, and they agree with each other at 33 MeV within the experimental uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…However, a measurement [15] of photon elastic scattering from He has constrained the total photoabsorption cross section, finding it to be larger than the sum of the FB o(y,p) measurements and the CBD then the sum of o(y,p) and cr(y, n) should give the total photoabsorption cross section. The situation has become even more controversial since yet another remeasurement [9] of cr(y, p) was found to be consistent with the original CBD values.…”
mentioning
confidence: 98%